TRAJETÓRIAS DE ESCOLARIZAÇÃO DE JOVENS QUE ABANDONARAM O PROJOVEM: por que não prosseguiram o caminho? - Martins, Talita de Jesus da Silva (2013)
This work focuses on the research trajectory of schooling of young people who left the National Youth Inclusion Programme - ProJovem held in São Luís - MA, in its first two years of implementation (2005-2007), with the intention of analyzing determinants influencing the nonlinearity of their trajectories. In this sense, for composition of theoretical and methodological framework are deepened public policy categories of social inclusion, youth, schooling and school dropouts from studies based on: Abad, 2002; Abramo, 1997; Dayrell, 2007; Charlot, 2000; Lahire, 1997; Nogueira, 2002; Patto, 2010 and others. The methodology is guided from a qualitative perspective, using studies of trajectories, as we had intended to go in search of the dynamics of relationships and perceptions of these young people about education. Was used as a research tool for data collection and information semistructured interviews with young people who have left the program because it is recognized that this is an important tool in the study of trajectories, the measure that allows us to identify the singularities present in each individual, ie, the various ways of acting and thinking of young people, this is an essential factor to be taken into account particularly in the study of trajectories. Thus, this research is that no - contact element can be identified as the sole cause of failure situation where young people met or are still, and that each element only has meaning or purpose in natural settings. Therefore, the determinants cited in the survey as: pregnancy, violence in neighborhoods, jealous spouse, lack of parental support, it was found that the school has become an unattractive place for young students, although some have taken up studies and concluded high school and others may express their wish to return to study.